Dynamics of Enceladus and Dione inside the 2:1 mean-motion resonance under tidal dissipation - Callegari, N. [UNESP]; Yokoyama, T. [UNESP] (Springer, 2008)
In a previous work (Callegari and Yokoyama, Celest. Mech. Dyn. Astr. 98:5-30, 2007), the main features of the motion of the pair Enceladus-Dione were analyzed in the frozen regime, i.e., without considering the tidal evolution. Here, the results of a great deal of numerical simulations of a pair of satellites similar to Enceladus and Dione crossing the 2:1 mean-motion resonance are shown. The resonance crossing is modeled with a linear tidal theory, considering a two-degrees-of-freedom model written in the framework of the general three-body planar problem. The main regimes of motion of the system during the passage through resonance are studied in detail. We discuss our results comparing them with classical scenarios of tidal evolution of the system. We show new scenarios of evolution of the Enceladus-Dione system through resonance not shown in previous approaches of the problem.
Keywords: Enceladus; Dione; Mean-motion resonance; Satellites; Saturn satellites; Tidal evolution